Development of an Encyclopedia Book for Anatomy and Morphology of Plants on the Morphological Identification of Orchid Plants (Orchidaceae) in Kampoeng Anggrek Kediri - Rizky Intan Adina Putri; Haslinda Yasti Agustin (Universitas Islam Negeri Walisongo Semarang, 2023)
The low level of understanding of biology students on plant morphology material, especially Orchidaceae, requires the development of learning resources. This study aims to develop an encyclopedia